Pendekatan Kearifan Lokal pada Aspek Sosial di Wisata Malam Kota Berastagi - Selly Veronica (Jurnal Abdimas Pariwisata, 2020)
Local Wisdom Approach on Social Aspect in Berastagi Night Tourism. Tourism is a strategic sector that becomes a significant part of urban development. Night tourism is the kind of tourism which innovative and potential to develop. Berastagi is known as one of the popular tourist destinations in North Sumatra that has night tourism. But nowadays, the negative image of night tourism that attaches to community life always be an obstacle in its developing process. Applying the local wisdom approach in the social aspect of night tourism is necessary to be held to create harmony between night tourism and community. The descriptive qualitative analysis has been carried out using the data collecting method by interview and field observation. This study shows local wisdom be the strength and protection that the community has to support the night tourism development in Berastagi.